Identification and Urgent Management Critical in TIA - Nichols, Emma Hitt (MD Conference Express, 2014)
Although the diagnosis of transient ischemic attack (TIA) can be challenging, identifying potential TIAs is imperative for urgent evaluation and treatment for preventing stroke. This article discusses the management of patients with TIA with particular focus on assessment of stroke risk.